Investigation of intelligent reflecting surfaces using lumped elements for 5G wireless communication networks - Alias, Nur Asyiqin; Abdul Malek, Norun Farihah; Bashri, Mohd Saiful Riza; Abdul Rahman, Farah Diyana; Mohd. Ramli, Huda Adibah; Azemi, Saidatul Norlyana; Islam, Md. Rafiqul (IEEE, 2025)
In this study, an Intelligent Reflecting Surface (IRS) has been designed to operate at 3.5 GHz, featuring a compact unit cell measuring 42 mm x 42 mm with a Circular Patch and Ring configuration. The metasurface utilizes an FR- 4 substrate with a dielectric constant of 4.3, a loss tangent of 0.008, and copper as the ground plane. A lumped element is incorporated into the unit cell to function as a switch in both ON (1) and OFF (0) states. Four positions have been identified for the ON OFF resulting to 16 bits configurations. The SParameter is the primary focus of the analysis. At 3.5 GHz, for a unit cell using Floquet port simulation indicated that the 0000- bit configuration exhibited the highest reflection efficiency with an S11 magnitude of -0.7534 dB and a phase shift of -16.7°. This result suggests that the unit cell design with lumped elements perform well as a reflector, with the S11 magnitude approaching 0 dB indicating effective gain.